Effectiveness of Chemopreventive and Life Style as Breast Cancer Prevention: a Literature Review - Min, Diya; Alfajri, Asri; Nurul, Fika; Mugi, Virjinia; Husna, Zahira; Pradani, Ninda (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Background: Breast cancer is the most common cancer in women worldwide, including Indonesia. Breast cancer patients have an inherited genetic predisposition, including mutations in genes such as BRCA1 and BRCA2. Breast cancer prevention can be done through various ways, such as healthy lifestyle changes, early screening, and chemopreventive. Purpose : This study aims to assess various breast cancer prevention strategies, both through chemopreventive and lifestyle modification to determine the effectiveness of each treatment. Methods: This study used the PRISMA-ScR method (Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews). Article searches were in the form of English articles relevant to the research theme with data for the last 5 years (2020-2024) and types of articles Randomized controlled trial, case control, and prospective cohort studies through PubMed, Science direct, and SpringerLink. Results: This study shows that chemopreventive, particularly low-dose tamoxifen, and lifestyle modification are promising approaches in preventing breast cancer. Low-dose tamoxifen was shown to be effective in lowering breast cancer risk with milder side effects and improved patient compliance. In addition, lifestyle modifications such as healthy diet and physical activity also play an important role in breast cancer prevention. Conclusion: The combination of chemopreventive and lifestyle modification can be a comprehensive strategy to reduce the risk of breast cancer.